Excitons: Modulation of New Excitons in Transition Metal Dichalcogenide‐Perovskite Oxide System (Adv. Sci. 12/2019). Issue 12 (19th June 2019) - Yin, Xinmao; Yang, Ming; Tang, Chi Sin; Wang, Qixing; Xu, Lei; Wu, Jing; Trevisanutto, Paolo Emilio; Zeng, Shengwei; Chin, Xin Yu; Asmara, Teguh Citra; Feng, Yuan Ping; Ariando, Ariando; et al.
Abstract : In article number1900446, Shi Jie Wang, Wenjing Zhang, Andrivo Rusydi, Andrew T. S. Wee, and co‐workers observe high‐energy excitons that are generated by a new mechanism in monolayer‐MoS2 on SrTiO3, which are attributed to the change in many‐body interactions that couples with interfacial orbital‐hybridization. The interfacial interactions lead to a fermi‐surface feature at the interface. The results provide an understanding of 2D‐transition metal dichalcogenides heterointerfaces and show the crucial role that many‐body interactions play at the atomic level.